Anti-Judaism and Christian Orthodoxy: Ephrem’s Hymns in Fourth-Century Syria. By Christine Shepardson - Morrison, Craig E. (The journal of theological studies, 2010)
In the first edition of his Symbols of Church and Kingdom (Cambridge: Cambridge University Press, 1975), Robert Murray wrote that Ephrem ‘hated the Jews’ (p. 68). He was not the first scholar to notice Ephrem’s anti-Jewish rhetoric that some have likened to modern day anti-Semitism (see K. H. Kuhlmann, ‘The Harp out of Tune: The anti-Judaism/anti-Semitism of St. Ephrem’, The Harp 17 [2004], pp. 177–83). For several decades now, scholars have studied Ephrem’s works in order to discern the historical context that drove his anti-Jewish polemic. Murray thought Ephrem feared ‘the Rabbis’ influence with his flock’ (p. 67). H. J. W. Drijvers (‘Jews and Christians at Edessa’, JJS 36 [1985], p. 87) concluded that Ephrem was addressing Christians who were drawn to Jewish customs.